Neighbourhood environment correlates of physical activity: a study of eight Czech regional towns - Sigmundová, Dagmar; El Ansari, Walid; Sigmund, Erik (International journal of environmental research and public health, 2011)
An adequate amount of physical activity (PA) is a key factor that is associated with good health. This study assessed socio-environmental factors associated with meeting the health recommendations for PA (achieving 10,000 steps per day). In total, 1,653 respondents randomly selected from across eight regional towns (each >90,000 inhabitants) in the Czech Republic participated in the study. The ANEWS questionnaire assessed the environment in neighbourhoods, and participants' weekly PA was objectively monitored (Yamax Digiwalker SW-700 pedometer). About 24% of participants were sufficiently active, 27% were highly active; 28% participants were overweight and 5% were obese. Although BMI was significantly inversely associated with the daily step counts achieved only in females, for both genders, BMI was generally not significantly associated with the criterion of achieving 10,000 steps per day during the week. Increased BMI in both genders was accompanied with a decline in participation in organized PA and with increasing age. As regards to the demographic/lifestyle factors, for females, more participation in organized PA was significantly positively correlated with the achieved daily step counts. In contrast, older age and higher BMI (for females) and smoking (for males) were significantly negatively correlated with the achieved daily step counts. In terms of the environmental aspects, pleasant environments were significantly positively correlated to daily step counts for both genders. Additionally, for males, better residencies (more family homes rather than apartment blocks) in the neighbourhood were significantly positively correlated with their daily step counts. For females, less accessibility of shops and non-sport facilities (depending on walking distance in minutes) were significantly negatively correlated to the achieved daily step counts. Individuals who lived in pleasant neighbourhoods, with better access to shops and who participated in organized PA (≥ 2 times a week) tended to meet the recommendations for health-enhancing PA levels. The creation of physical activity-friendly environments could be associated with enhancing people's achieved daily step counts and meeting the health criteria for PA.
Keywords: dospělí; BMI; zdravotní politika; Female; charakteristiky bydlení; number of steps; Age Factors; Adult; ženské pohlaví; mladý dospělý; průřezové studie; Adolescent; Obesity; věkové faktory; lidé; Yamax pedometer; cvičení; Health Policy; Residence Characteristics; physical activity; Cross-Sectional Studies; ANEWS; obezita; Male; Czech Republic; Walking; Socioeconomic Factors; Young Adult; index tělesné hmotnosti; Česká republika; neighbourhood; lidé středního věku; socioekonomické faktory; environment; mužské pohlaví; Body Mass Index; Exercise; Czech population; Middle Aged; mladiství; chůze; Humans